The Role of Indigenous Languages in Schools: The Case of Sarawak - Ting, Su Hie; Campbell, Yvonne Michelle (Springer Singapore, 2017)
This chapter describes the role of indigenous languages in Sarawak schools, beginning with a brief background on the diversity of languages and indigenous language use patterns in the state. This is followed by a description of efforts to preserve and promote the formal learning of indigenous languages in various indigenous communities, with a special focus on the Bidayuh and Iban communities whose languages have been used for formal education. Efforts to preserve Sarawak indigenous languages in the early twentieth century took the form of producing orthography for the language. The Iban language has been standardised and offered as a school subject but it is more difficult for Bidayuh to become a school subject due to the regional variations in Bidayuh isolects. In recent years, Bidayuh has been introduced as a medium of instruction in some preschools run by the Dayak National Bidayuh Association. The other Sarawak indigenous languages have some written materials in their languages but they are far from integrating into the Malaysian national curriculum. The initial effort in this direction has to come from the indigenous communities but research has shown that belief in the heritage value of indigenous languages alone is not sufficient to mobilise community literacy activities on a long-term basis.